New venture development: The costs and benefits of public sector assistance - Chrisman, James J; Hoy, Frank; Robinson, Richard B (Journal of Business Venturing, 1987)
In recent years there has been an extraordinary level of entrepreneurial activity occurring in the United States. Venture start-ups, new incorporations even bankruptcies are reaching record numbers. Concurrent with the increase in entrepreneurial activity has been an effort within the Reagan Administration to privatize public sector programs designed to aid new and small, ongoing business ventures. The premise behind this movement is that private sector initiatives can better, and more efficiently, serve the needs of entrepreneurs and small business managers and can also offer new business opportunities for some entrepreneurs. At the same time, however, privatization could reduce the assistance programs currently targeting fledgling ventures, many of which are unable to afford a private consultant. The purpose of this article is to examine the economic impact of one public sector assistance program, the Small Business Development Center (SBDC), in terms of its contributions to new venture initiation in Georgia and South Carolina. The focus on the SBDC program is appropriate since over 50% of the counseling activities of most of the centers is devoted to pre-venture clients, i.e., individuals or groups considering starting a business. This study is important and timely, not only in respect to assessing the effectiveness of public sector assistance programs for pre-ventures, but also for assessing whether it is worthwhile from an economic perspective, to offer assistance to such individuals in the first place. Although it is difficult to be precise in attributing cause to effects in dynamic business ventures, our study indicates that the Small Business Development Center's client sample experienced a greater than expected number of business starts, and a higher than expected rate of survival. The results suggest that the net taxable sales, generated by these new ventures in 1984. was approximately $20 million in Georgia and $10 million in South Carolina. Results also suggest that almost 500 new jobs were created in Georgia and 600 new jobs were created in South Carolina between 1981 and 1984 as a result of successful business starts among SBDC pre-venture clients. While such figures are impressive, the bottom line of this study is that the new tax revenues generated by client firms exceeded the cost of delivering the services. Specifically, our conservative estimates suggest a $3.80 to $1.00 and $1.50 to $1.00 benefit to cost ratio for the center's pre-venture consulting services in Georgia and South Carolina, respectively. Furthermore, the value attached to the assistance received, by the entrepreneurs themselves, closely paralleled our estimates, lending additional validity to our conclusions. Resource constrained entrepreneurs can obtain effective business assistance from the SBDC free-of-charge, and the benefits to society accruing from this service far outweigh the cost of providing them.